Life Stages, Gender and Temporalities. Historical and Sociological Reflections - Charles, Aline; Charton, Laurence (Enfances, Familles, Générations, 2017)
Research Framework: Long conducted in parallel, studies on life stages and gender have converged more in recent years, but still leave large areas uncovered. Some analyzes still treat sex as a simple variable that does not require problematization. Others lose sight of the fact that growing up and aging generate categories and trajectories that are the result of interactions of sex and age. The link between gender and age thus still needs to be tightened. Objectives: The introductory article of the issue " Life Stages, Gender and Temporalities" proposes to explore the interactions between age and gender relations by examining the gendered constructions of ages and the life trajectories structured by gender. Methodology: This article lists studies by sociologists and historians exploring gender/age links. Results: The articles presented help to show to what extent gender and age relationships overlap and interact in the development of social inequalities throughout the life of individuals. They also participate in questioning the social hierarchy which is "mechanically" based on gender and certain age-related markers. Conclusions: The joint analysis of gender and age relations is progressing, but slowly, and still remains in the blind spot of intersectional perspectives. While current research now recognizes gender and age as constantly interacting systems, it too seldom addresses the power relations and the cumulative inequalities they generate. Contribution: This introductory article opens up new research perspectives, both with regard to the gendered processes favouring the development of sexual physical characteristics and to the dominant social codes that shape heteronormative experiences and temporalities.